2022
DOI: 10.1093/stmcls/sxac059
|View full text |Cite
|
Sign up to set email alerts
|

PDGFRα/Sca-1 Sorted Mesenchymal Stromal Cells Reduce Liver Injury in Murine Models of Hepatic Ischemia-Reperfusion Injury

Abstract: Liver transplantation is an effective therapy, but increasing demand for donor organs has led to the use of marginal donor organs with increased complication rates. Mesenchymal stromal cells (MSC) pleiotropically modulate aberrant immune-mediated responses and represent a potential therapy to target the inflammation seen post-transplant with marginal donor livers. To avoid the confounding effects of xenotransplantation seen in studies with human MSC, a PDGFRα/Sca-1 (PaS) sorted MSC population was used which wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Numerous previous studies have demonstrated the importance of endogenous PDGFR–β signaling in vascular development and tissue repair, whereas the function of PDGFR–β signaling in exogenous transplanted therapeutic cells remains poorly understood. Andrew Owen et al reported that PDGFR–α positive MSCs had a better therapeutic effect on a rat model of hepatic ischemia-reperfusion [ 36 ], and Wang Feng et al demonstrated that PDGFR–α positive BMSCs can secrete more mir–6924–5p, which can better treat osteolysis and improve healing intensity during tendon bone healing [ 37 ]. Consequently, as a member of the PDGFRs family, what effect does PDGFR–β signaling have on the function and therapeutic potential of ADSCs?…”
Section: Discussionmentioning
confidence: 99%
“…Numerous previous studies have demonstrated the importance of endogenous PDGFR–β signaling in vascular development and tissue repair, whereas the function of PDGFR–β signaling in exogenous transplanted therapeutic cells remains poorly understood. Andrew Owen et al reported that PDGFR–α positive MSCs had a better therapeutic effect on a rat model of hepatic ischemia-reperfusion [ 36 ], and Wang Feng et al demonstrated that PDGFR–α positive BMSCs can secrete more mir–6924–5p, which can better treat osteolysis and improve healing intensity during tendon bone healing [ 37 ]. Consequently, as a member of the PDGFRs family, what effect does PDGFR–β signaling have on the function and therapeutic potential of ADSCs?…”
Section: Discussionmentioning
confidence: 99%
“…Tail vein ( 165 , 166 ), hepatic vein ( 167 ) and peripheral vein ( 168 ) injection of MSCs in an ischaemia-reperfusion injury animal model showed that MSC infusion can reduce liver damage and cell death ( 165 , 167 ), improve the levels of ALT and AST ( 166 168 ) and mainly decrease oxidative stress caused by liver excision and ischaemia-reperfusion injury ( 169 ). MSCs also inhibit the production of proinflammatory cytokines (TNF-α, IL-1β and iNOS), macrophage activation and neutrophil recruitment and promote anti-inflammatory cytokine secretion (IL-10), which is beneficial for recovery from liver injury and inflammatory responses ( 167 ).…”
Section: Developing Animal Models Of Liver Failure and The Mechanism ...mentioning
confidence: 99%